A Hypothesis About the Role of Adult Neurogenesis in Hippocampal Function - Schinder, Alejandro Fabián (2004)
The functional relevance of adult hippocampal neurogenesis has long been a matter of intense experimentation and debate, but the precise role of new neurons has not been sufficiently elaborated. Here we propose a hypothesis in which specific features of newly generated neurons contribute to hippocampal plasticity and function and discuss the most recent and relevant findings in the context of the proposed hypothesis.